Contribution of Surface Treatment on Physical and Mechanical Properties of Recycled Concrete Aggregates - Brian Jacks Odero; Raphael N. Mutuku; Timothy Nyomboi; Zachary A. Gariy (Advances in Civil Engineering)
The demand for virgin aggregates for concrete production worldwide has been increasing. At the same time, there is an increase in the production of rubbles from construction-related activities. The residues are produced either due to leftovers or from the demolished structures. However, worldwide, the utilization of recycled concrete aggregate (RCA) material for structural concrete has been limited, often considered inferior due to distorted surfaces. The problems with RCA arise because it is a composite aggregate made of natural aggregate and cement, and adhered surface mortar is the discontinuities on the surface that arise from the production technique or the strength of the original concrete. The development of hydrated calcium silicate binder in the concrete matrix has been the critical desire of researchers to make better concrete material. This research focuses on the treatment of RCA from locally available rice husk ash with minimum pozzolanic cement. The objective was achieved by conducting tests on the properties of aggregates that include specific gravity and water absorption, aggregate crushing value (ACV), and aggregate impact value (AIV). The effectiveness of the treatment technique is assessed by the analysis of SEM imagery and XRD analysis of the microstructure cement paste around the RCA. At 20% pozzolan concentration, RCA treatment yields comparable specific gravities, water absorption, ACV, and AIV. Furthermore, the replacement of 5% rice husk ash (in 20% concentration) provided the optimal proportion of treatment for RCA, resulting in a reduction of ACV by 31.4%, AIV by 30.0%, and water absorption by 12.7% compared to the untreated RCA. XRD showed that calcite (CaCO₃), quartz, and portlandite phases were the majority in the untreated RCA. The study indicates that pozzolanic cement with 15% can be used with 5% RHA to produce RCA with characteristics almost similar to virgin aggregates. This research presents a consistent methodology to achieve modified RCA for application in construction.